Synthesis of CdS Nanocrystalsin the Gelatin Matrix with Different рН Values and their Optical Properties - Boshernitsan, V.I.; Smyntyna, V.A.; Skobeeva, V.M.; Malushin, N.V. (Physics and Chemistry of Solid State, 2015)
We have investigated the influence of solution pH on the formation of nanocrystals and their size in the process of synthesis. We have analyzed the optical absorption spectra and luminescence of colloidal solutions of NC CdS.Nanocrystals of cadmiumsulphide were obtained by sol-gel technology in gelatin solution which has different pH values ​​(6 ÷ 10). A decrease was observed in the average size of the nanocrystals from 8 till 3.5 nm while reducing pH from 10 to 6. There has been established the dependence of the contour of luminescence spectra from pH values.